The Problem of the Transformation of the Public Space in the Theories of H. Arendt and J. Habermas - Alijauskaitė, Agnė (Sociologija. Mintis ir veiksmas, 2017)
This paper briefly introduces the concepts of the public space by H. Arendt and J. Habermas, compares them and presents an analysis of the problems concerning the transformation of the public space. In this work, I try to demonstrate that a confrontation between the civic body and the state that appears in the context of the transformation of the public space is not completely grounded. The public sphere, which connects these two areas, is not autonomous. For the main points, I choose the theories of the two authors – Hannah Arendt and Jürgen Habermas. In the work, I discuss the similarities and differences of these theories as well as their conceptual interactions.